DAYA SERAP MANGROVE Avicennia marina TERHADAP LOGAM BERAT KADMIUM (CD) DAN TIMBAL (PB) DI KAMPUNG NELAYAN KECAMATAN MEDAN BELAWAN SUMATERA UTARA - Vinces Agriani Lase; Yunasfi Djayus; Desrita Desrita (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2016)
Human and industry activities in Nelayan Village can be increasing the present of heavy metal in acuatiq environmental and can put on effect to aquatic organism. The purpose of this research is to analyze the content of heavy metals Cadmium (Cd) and Plumbum (Pb) on roots, barks, leaves and knowing the ability of A. marina in accumulating heavy metals. The sample was taken from Nelayan Village, District of Medan Belawan. The analysis of heavy metals Cd dan Pb is carried out in Balai Riset dan Standarisasi Industri Medan, by using the Atomic Absorption Spectrofotometer (AAS) method. The results of this research indicated that the heavy metal content of Pb in the roots, barks, and leaves is larger more than Cd. Based on the bioconcentration factor, the ability of A. marina in accumulate heavy metals Cd and Pb categorized low.Keywords : AAS, Avicennia marina, Cadmium (Cd), Heavy Metal, Plumbum (Pb)